Leverage dan Sales Growth terhadap Financial Distress dengan Moderasi Profitabilitas Pada Perusahaan Ritel yang terdaftar di Bursa Efek Indonesia Tahun 2019-2022 - Sari, Annisa Devy Kartika; Hidajat, Taofik (EconBank: Journal of Economics and Banking, 2024)
The study aims to identify the impact of leverage and sales growth on financial distress with profitability as a moderation variable in retail companies listed on the Indonesian Stock Exchange. There are 19 retail firms listed on the Indonesia Stock Exchange that are used as a sample in this study with a research period of 4 years, namely 2019–2022. This type of research is quantitative, with data analysis techniques using double linear regression analysis and moderating regression analysis (MRA) with the help of SPSS applications. The results conclude that leverage and sales growth have no influence on financial distress.